2016
DOI: 10.1093/mnras/stw2447
|View full text |Cite
|
Sign up to set email alerts
|

On the black hole mass of the γ-ray emitting narrow-line Seyfert 1 galaxy 1H 0323+342

Abstract: Narrow-line Seyfert 1 galaxies have been identified by the Fermi Gamma-Ray Space Telescope as a rare class of γ-ray emitting active galactic nuclei (AGN). The lowestredshift candidate among them is the source 1H 0323+342. Here we present quasisimultaneous Gemini near-infrared and Keck optical spectroscopy for it, from which we derive a black hole mass based on both the broad Balmer and Paschen emission lines. We supplement these observations with a NuSTAR X-ray spectrum taken about two years earlier, from whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 59 publications
10
42
0
Order By: Relevance
“…The estimate of the mass of the central black hole in narrow-line Seyfert 1 Galaxies is at the center of a long-standing debate (see [10] and references therein for the latest information). In the case of J0324 + 3410, the values are of the order of 10 7 M ( [1,2,11,13,12]), with two exceptions [9,14]. The available values and adopted methods are summarised in Table 1.…”
Section: Mass Of the Central Black Holementioning
confidence: 99%
“…The estimate of the mass of the central black hole in narrow-line Seyfert 1 Galaxies is at the center of a long-standing debate (see [10] and references therein for the latest information). In the case of J0324 + 3410, the values are of the order of 10 7 M ( [1,2,11,13,12]), with two exceptions [9,14]. The available values and adopted methods are summarised in Table 1.…”
Section: Mass Of the Central Black Holementioning
confidence: 99%
“…Deep X-ray spectroscopy with the X-ray observatories XMM-Newton, Suzaku, and NuSTAR of selected sources has revealed that most radio-loud NLS1 galaxies studied thus far show significant soft X-ray emission components, that are most plausibly related to the accretion disc (e.g., [50], [36], [58], [29], [114], [110], [147], [54], [89], [85], [55], [91]; Fig. 4b), but apparently absent in a few cases, at least at some epochs (PKS2004-447: [110], [83]; SDSSJ2118-0732: [146]).…”
Section: Spectroscopy and Variabilitymentioning
confidence: 99%
“…[156] estimated M BH = 10 7 M based on a single-epoch Hβ spectrum. [89] used broad Pα and derived 2 10 7 M . Reverberationmapping with the Lijiang telescope gave 6 10 6 M ( f BLR = 1) or 3 10 7 M ( f BLR = 6, [139]).…”
Section: Black Hole Massesmentioning
confidence: 99%
“…One of its most interesting features is its frequent variability both in X-rays and gamma-rays which, although often uncorrelated, sometimes presents hints of correlation (Paliya et al, 2014). The black hole mass is M BH = 2 × 10 7 M ⊙ (Landt et al, 2017), and the viewing angle was estimated to be θ ∼ 4 • − 13 • in Fuhrmann et al (2016). For our models, we arbitrarily fixed θ = 5 • .…”
Section: H 0323+342mentioning
confidence: 99%
“…Average Swift XRT and UVOT data from observations taken in September 2013 and December 2014 with NuSTAR data from March 2014 (see Landt et al, 2017 for further details) and Fermi data from the low state in Paliya et al (2014) are considered as the quiescent state of the source, depicted in light green in Figure 2. Simultaneous Fermi-LAT from August 27th 2013 to August 31st 2013 and Swift UVOT and XRT data from Paliya et al (2014) are taken into account for the flaring state (orange data points and bow-tie in Figure 2).…”
Section: Data Sample and Analysismentioning
confidence: 99%